Spatial and seasonal variations in C3Hx hydrocarbon abundance in Titan’s stratosphere from Cassini CIRS observations - Lombardo, NA; Nixon, CA; Achterberg, RK; Jolly, A; Sung, K; Irwin, PGJ; Flasar, FM (Elsevier, 2018)
Of the C3Hx hydrocarbons, propane (C3H8) and propyne (methylacetylene, CH3C2H) were first detected in Titan’s atmosphere during the Voyager 1 flyby in 1980. Propene (propylene, C3H6) was first detected in 2013 with data from the Composite InfraRed Spectrometer (CIRS) instrument on Cassini. We present the first measured abundance profiles of propene on Titan from radiative transfer modeling, and compare our measurements to predictions derived from several photochemical models. Near the equator, propene is observed to have a peak abundance of 10 ppbv at a pressure of 0.2 mbar. Several photochemical models predict the amount at this pressure to be in the range 0.3–1 ppbv and also show a local minimum near 0.2 mbar which we do not see in our measurements. We also see that propene follows a different latitudinal trend than the other C3 molecules. While propane and propyne concentrate near the winter pole, transported via a global convective cell, propene is most abundant above the equator. We retrieve vertical abundances profiles between 125 km and 375 km for these gases for latitude averages between 60°S–20°S, 20°S–20°N, and 20°N–60°N over two time periods, 2004 through 2009 representing Titan’s atmosphere before the 2009 equinox, and 2012 through 2015 representing time after the equinox. Additionally, using newly corrected line data, we determined an updated upper limit for allene (propadiene, CH2CCH2, the isomer of propyne). We claim a 3-σ upper limit mixing ratio of 2.5  ×  10 within 30° of the equator. The measurements we present will further constrain photochemical models by refining reaction rates and the transport of these gases throughout Titan’s atmosphere.